Planting Base Value of Hardworking Character Education through Ulid Novel - Hidayat Nur Septiadi; Andayani Andayani; Nugraheni Eko Wardani (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Important hard work characters are taught for the younger generation today so that researchers are interested in describing and explaining the values of character education in hard work in Ulid's novel by Mahfud Ikhwan. This novel tells the story of the struggle of poor families to send their eldest children from kindergarten to high school with various struggles and hard work in his life. The actions that the characters to bring out the character values of hard work that are proven through the attitude and every dialogue of the characters. This study included descriptive qualitative with note-taking techniques and literature studies. The results of data analysis of hard work character values are known to 9 frequencies, including unyielding characters, passionate characters, active working characters, earnest characters, the full character of confidence in acting, the full character of the struggle for life, independent practice character, cooperative character, and characters fight together.